2018
DOI: 10.1158/0008-5472.can-17-2900
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I and II Diversity Contributes to the Etiologic Heterogeneity of Non-Hodgkin Lymphoma Subtypes

Abstract: A growing number of loci within the human leukocyte antigen (HLA) region have been implicated in non-Hodgkin lymphoma (NHL) etiology. Here, we test a complementary hypothesis of "heterozygote advantage" regarding the role of HLA and NHL, whereby HLA diversity is beneficial and homozygous HLA loci are associated with increased disease risk. HLA alleles at class I and II loci were imputed from genome-wide association studies (GWAS) using SNP2HLA for 3,617 diffuse large B-cell lymphomas (DLBCL), 2,686 follicular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
3
27
1
Order By: Relevance
“…The HLA region is critical for innate and adaptive immune response and has a complex relationship with cancer risk. Heterogeneous associations with HLA haplotypes have been reported for different subtypes of NHL 44 and lung cancer 45 , suggesting that relevant risk variants are likely to differ within, as well as between, cancers. Studies have further demonstrated that somatic mutation profiles are associated with HLA class I (ref.…”
Section: Discussionmentioning
confidence: 99%
“…The HLA region is critical for innate and adaptive immune response and has a complex relationship with cancer risk. Heterogeneous associations with HLA haplotypes have been reported for different subtypes of NHL 44 and lung cancer 45 , suggesting that relevant risk variants are likely to differ within, as well as between, cancers. Studies have further demonstrated that somatic mutation profiles are associated with HLA class I (ref.…”
Section: Discussionmentioning
confidence: 99%
“…An initial evaluation of HLA zygosity based on allelotyping data reported increased risk of DLBCL with HLA class I zygosity among a U.S. Caucasian population of 163 DLBCL patients (Table ) . A GWAS‐based evaluation of HLA zygosity which leveraged imputed HLA data with 3,617 DLBCL patients confirmed the elevation of DLBCL risk with increasing number of HLA class I alleles and further observed increasing DLBCL risk associated with HLA class II alleles as well as zygosity across HLA‐B , HLA‐C , HLA‐DRB1 and HLA‐DQB1 . However, among transplant recipients, Hussain and colleagues reported no association among HLA class I or II zygosity .…”
Section: Diffuse Large B‐cell Lymphomamentioning
confidence: 99%
“…Only one report of zygosity has been reported to date for FL risk, reporting increased FL risk for zygosity in HLA class II alleles, both overall across alleles ( P ‐trend < 0.0001) and individually ( HLA‐DRB1 : OR = 1.54, 95% CI = 1.31–1.82; HLA‐DQB1 : OR = 1.42, 95% CI = 1.23–1.65; HLA‐DPB1 : OR = 1.24, 95% CI = 1.10–1.40) (Table ) . Although conducted among 2686 FL patients and 8,753 controls, replication of these results is needed.…”
Section: Follicular Lymphomamentioning
confidence: 99%
See 2 more Smart Citations